Time-series clustering – A decade review - Aghabozorgi, Saeed; Seyed Shirkhorshidi, Ali; Ying Wah, Teh (Information systems (Oxford), 2015)
Clustering is a solution for classifying enormous data when there is not any early knowledge about classes. With emerging new concepts like cloud computing and big data and their vast applications in recent years, research works have been increased on unsupervised solutions like clustering algorithms to extract knowledge from this avalanche of data. Clustering time-series data has been used in diverse scientific areas to discover patterns which empower data analysts to extract valuable information from complex and massive datasets. In case of huge datasets, using supervised classification solutions is almost impossible, while clustering can solve this problem using un-supervised approaches. In this research work, the focus is on time-series data, which is one of the popular data types in clustering problems and is broadly used from gene expression data in biology to stock market analysis in finance. This review will expose four main components of time-series clustering and is aimed to represent an updated investigation on the trend of improvements in efficiency, quality and complexity of clustering time-series approaches during the last decade and enlighten new paths for future works. •Anatomy of time-series clustering is revealed by introducing its 4 main component.•Research works in each of the four main components are reviewed in detail and compared.•Analysis of research works published in the last decade.•Enlighten new paths for future works for time-series clustering and its components.